PELATIHAN PENYUSUNAN E-LKPD BERBASIS LIVEWORKSHEET BAGI GURU SMP DI KECAMATAN LEIHITU BARAT MALUKU TENGAH - Matitaputty, Christi; Ramadhani, Widya Putri; Anastasyia, Neneng; Pattiasina, Florentine Gratia; Laurika, Priciliya Ademaya (Universitas Pattimura, 2025)
The Electronic Student Worksheet (e-LKPD), utilizing a digital learning platform Liveworksheet offers a significant opportunity for digital transformation in education. This Community Service (PkM) activity aimed to enhance the digital competence of junior high school teachers in Leihitu Barat District, Central Maluku, in developing e-LKPDs that provide students with a more interactive learning experience. The methods used included socialization, training, technology implementation, mentoring, and evaluation. The Liveworksheet-based e-LKPD training successfully improved teachers’ digital literacy and produced interactive teaching materials that are engaging, efficient, and easily accessible for students. The use of e-LKPD increases student participation in the classroom learning process by up to ±65% and speeds up teacher learning evaluation. The integration of local wisdom into digital content made learning more contextual while also supporting the preservation of Maluku’s cultural heritage